Academic Achievement Among Children With Nonsyndromic Orofacial Clefts: A Population-Based Study. (January 2018) - Watkins, Stephanie E.; Meyer, Robert E.; Aylsworth, Arthur S.; Marcus, Jeffrey R.; Allori, Alexander C.; Pimenta, Luiz; Lipinski, Robert J.; Strauss, Ronald P.
Objective: Children with orofacial clefts (OFCs) may experience poor reading proficiency, learning disabilities, and academic underachievement. We examined the association between nonsyndromic (NS) OFCs and end-of-grade (EOG) performance in reading and math from third through eighth grade in a sample subgroup. Participants: We identified a cohort of 559 children with NS-OFCs and 6822 children without birth defects, classifying cleft type by cleft lip alone, with or without cleft alveolar ridge (CL); cleft lip with cleft palate (CL+P); and cleft palate only (CP). Main Outcome Measures: Using logistic regression, we estimated the odds of not meeting grade-level standards among children with NS-OFCs compared to unaffected peers. Using longitudinal analyses, we estimated the odds of not meeting grade-level standards and average change in test scores through eighth grade. Results: Children with NS-OFCs were 1.22 (95% CI: 0.96, 1.83) times as likely not to meet grade-level standards in reading compared to unaffected peers. The effect was similar for math (OR: 1.17; 95% CI: 0.92, 1.48). Children with CL+P were 1.33 (95% CI: 0.86, 1.83) and 1.74 (95% CI: 1.19, 2.56) times as likely not to meet grade-level standard in reading and in both subjects, respectively, compared to unaffected peers. The average rate of change in both scores was similar for children with and without OFCs. Conclusions: Poor academic performance appears greatest for children with CL+P, a finding compatible with previous observations and hypothesized mechanisms associating orofacial clefts with subtle abnormalities in brain development. Academic performance monitoring and referral for academic assistance is warranted.